An investigation of effect of control jets location and blowing pressure ratio to control base pressure in suddenly expanded flows - Pathan, Khizar Ahmed; Dabeer, Prakash S; Khan, Sher Afghan (Yildiz Technical University Press, 2020)
The drag force is an essential factor in any projectile from road vehicles to rocket or aircraft. The total drag includes skin friction drag, wave drag, and base drag. The base drag is the drag due to low pressure in the base region of the projectile. In the case of suddenly expanded flows, due to the sudden expansion of flow from the nozzle into the enlarged duct, the low pressure is created in the base region of the enlarged tube, which results in base drag and hence overall thrust reduced. In this paper Computational Fluid Dynamic (CFD) analysis is used to analyze the effect of secondary air blowing jets called control jets to control base pressure in the base region of the suddenly enlarged duct. These control jets are placed at different Pitch Circle Diameters (PCD) on the base face of the enlarged pipe. The objective of this work is to increase the base pressure up to atmospheric pressure and hence reduces the base drag. Mach number 3.0 is considered for analysis. The CFD analysis is done for different combinations of Area Ratios (AR) (2, 5 and 8), Nozzle Pressure Ratios (NPR ) (2, 5 and 8) and PCD (d 1, d 2, and d3. Further analysis is done for different air blowing pressure ratios (BPR) to optimize air blowing pressure. The analysis results are plotted for different area ratios, nozzle pressure ratios, and PCD of control jets. By observing results, it can be concluded that the base pressure is strongly influenced by AR, NPR, and PCD of control jets. The air blowing pressure should be optimum to save energy, and the optimum values can be selected from the results.